Beetle boy - David, Lawrence; Durand, Delphine (New York : Doubleday Books for Young Readers, 1999)
After Gregory Sampson wakes up one morning to discover that he has become a giant beetle, only one person seems to notice.
Keywords: Beetles -- Fiction; Metamorphosis -- Ficiton